Safe Care for The Elderly With Complications After Spinal Surgery - วีระพงษ์, ณัฐธยาน์ (Journal of The Royal Thai Army Nurses, 2019)
Complications in the elderly after spinal surgery are common due to deteriorating health conditions and function of the body decline from use for a long time. The elderly is the greater risk for physical and mental problems. The purposes of this article were display nursing care in dimension of healthcare for safety caring in the elderly who underwent lumbar spinal surgery to reduce postoperative complications. Theoretical concepts related to factors affect common postoperative complications in the elderly. Nursing diagnosis for the elderly after lumbar spine surgery were display in case study model. Effective nursing care were display to cover physical, mental, emotional, and social.